Analyzing Eighth-grade Students' Numerical Literacy Skills in Problem Solving with Number Concepts - Pratiwi Dwi Warih Sitaresmi; Nuryami Nuryami; Imro Atus Soliha (JNPM (Jurnal Nasional Pendidikan Matematika), 2023)
Abstract. The aim of this study was to assess the numerical literacy abilities of eighth-grade students at MTs Miftahul Ulum in applying problem-solving skills to number concepts on a question-by-question basis. The research followed a qualitative methodology, and the participants consisted of 15 students from the VIIIA class at MTs Miftahul Ulum. The data were analyzed based on Polya's stages of problem-solving and numeracy literacy indicators. Data collection methods included numeracy literacy tests, interviews, and documentation. The results indicated that a significant proportion of students demonstrated a moderate level of numeracy literacy, while some students showed low or high levels of proficiency. Generally, the understanding stage had higher percentages of students who demonstrated comprehension. However, the planning and implementation stages varied across different questions. By focusing on the specific stages where students struggled or excelled, teachers can adapt their instructional approaches to better address students' needs. Keywords: Numerical Literacy, Polya, Numbers.